Acceptability of Grasshopper Nugget Flour as a High-Protein Functional Food - Sherly Maureta Santi; Mitha Faula Rusdiyana; Ria Novita Sari; Riska Nabela Andini Putri; Arya Ulilalbab; Nuzul Dwi Utami; Nining Tyas Triatmaja (Health Dynamics, 2025)
Background: Nugget products enhanced with locust flour are being explored as a novel source of functional food due to their high protein content, which plays a vital role in maintaining human health. Locusts, commonly consumed in parts of Africa and Asia, offer a promising alternative protein source. This study investigated the consumer acceptability of nuggets formulated with grasshopper flour as a nutrient-dense, functional food option. Methods: A Completely Randomized Design (CRD) was employed, and data were analyzed using the Friedman Test to assess differences among treatments. If significant differences (p < 0.05) were found, further analysis was performed with the Wilcoxon Test through SPSS version 20. Organoleptic evaluation was carried out by 30 semi-trained panelists. The nugget formulations tested were: P1 (100% tapioca flour, 0% grasshopper flour), P2 (95% tapioca flour, 5% grasshopper flour), and P3 (85% tapioca flour, 15% grasshopper flour). Results: Findings indicated that P1 (without grasshopper flour) received the highest scores in terms of color and aroma. For texture, both P1 and P2 (5% grasshopper flour) were equally preferred. In terms of taste, P1 remained the most favored. Conclusion: Overall, nuggets without any addition of grasshopper flour (P1) achieved the highest level of acceptability across all sensory attributes.